INNOVATION PROCESS MANAGEMENT IN HIGHER PEDAGOGICAL SCHOOL - Шарапанюк, Алина; Троян, Наталья (SWorldJournal, 2021)
The article reveals the essence of innovative pedagogical activity. It is proved that future teachers readiness to innovative activity is an integral characteristic, which includes realization of the value of innovative activity, knowledge of methodology,